1990
DOI: 10.1111/j.1365-3040.1990.tb02139.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal dynamics of carbohydrate and nitrogenous components in the roots of perennial weeds

Abstract: Chicory (Cichorium itttyhus L.) and dandelion (Taraxacutn officinale L.) are persistent weeds, the aerial portions of which do not survive in winter. However, subterranean tissues remain viable and facilitate the rapid resumption of growth in early spring. The source of nutrients for gr-owth prior to the establishment of foliage is the r-oots. Carbohydrate and N reserves are accrued during late summer and attturnn, r-espectively. Hydrolysis of Iructans during late autumn occurs coincidentally with incr-ements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 23 publications
2
44
0
1
Order By: Relevance
“…Starch is stored in the leaves during the day to counteract the otherwise high water potential that would result from a comparable amount of sugars in the leaves. Increased starch has been cited as useful in cold-hardening of temperate plants (Cyr, Brewley, and Dumbroff 1990), although this would be a secondary An analysis of percent accumulation of starch in the plant shows that roots typically held 10 percent or less of starch reserves during the growing season (except in August), with stembases accounting for between 5 and 30 percent of starch (Figure 11 a). Leaves accounted for 60 to 80 percent of starch reserves, with the majority (up to 52 percent) being in the petioles.…”
Section: Carbohydrate Mass Balance -Mass Per Unit Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Starch is stored in the leaves during the day to counteract the otherwise high water potential that would result from a comparable amount of sugars in the leaves. Increased starch has been cited as useful in cold-hardening of temperate plants (Cyr, Brewley, and Dumbroff 1990), although this would be a secondary An analysis of percent accumulation of starch in the plant shows that roots typically held 10 percent or less of starch reserves during the growing season (except in August), with stembases accounting for between 5 and 30 percent of starch (Figure 11 a). Leaves accounted for 60 to 80 percent of starch reserves, with the majority (up to 52 percent) being in the petioles.…”
Section: Carbohydrate Mass Balance -Mass Per Unit Areamentioning
confidence: 99%
“…Low levels of starch content in roots were also observed in the small-scale WES study. The tap root of some species can store considerable quantities of starch to promote early-season growth (e.g., chicory (20 percent starch) and dandelion (30 percent starch); Cyr, Brewley, and Dumbroff 1990). Even the unmodified roots of M. spicatum can store up to 20 percent starch (Titus and Adams 1979).…”
Section: Starchmentioning
confidence: 99%
“…Taraxacum officinale overwinters as seed or it retains a reduced basal rosette under snow cover (Cyr et al 1990). …”
Section: Growth and Developmentmentioning
confidence: 99%
“…The storage proteins usually compose a small part of the total nitrogen pool within the root; their accumulation is related to overwintering. Cyr and Bewley (1989, 1990a, 1990b suggested that, in herbaceous perennial species, some proteins can be used as a temporary nitrogen source to support plant growth when needed.…”
mentioning
confidence: 99%